Security Mechanism for CSMA/CD Networks: A Survey (International Journal of Advanced Research in Computer Science, 2017)
In this paper we study about security against various malicious attacks. In this we also represent some known feasible attacks. We also get information about secured communication for different mechanism which provide a secrecy, security and authentication to most of security issues. In some logical section we learn about an active repeater in CSMA/CD for network comparison for data transmission between two addresses. If no match occurs, the logic section controls the transmitter so that the transmitter switches from transmitting the data packet to the clock signal. For bidirectional routing message received from wired network and send it to wireless network. At the end we get comparison result for transmitted message to the received message to find if a collision has occurred. Keywords: CSMA/CD, Sensor Network, DTDV protocol.